Analisis Kandungan Bahan Organik Tanah Pada Lahan Kelapa Sawit di Pantai Labu - Satria Wardana, Tegar; Putra Pratama, Firzy; Aura Zalwa, Cut; Aksan, Aksan; Pakpahan, Samsul (Program Studi Agroteknologi, 2025)
Oil palm is a crucial commodity that plays a significant role in Indonesia's economy. However, the intensification of oil palm cultivation often leads to a decline in soil quality, particularly in terms of soil organic matter (SOM), which is essential for soil fertility and long-term productivity. Purpose of the research is organic matter content of soil in oil palm plantations in Pantai Labu, Deli Serdang Regency. The analysis was conducted using the Walkley and Black method, which involves the oxidation of organic carbon with potassium dichromate. Soil samples were gained at a depth of 0–20 cm also analyzed at the Palm Oil Technology Institute Laboratory. The results showed an organic carbon content of 1.248% and soil organic matter of 2.146%, which falls within the moderate category. Although the soil is still capable of supporting plant growth, these results highlight the importance of sustainable organic matter management. Utilizing plantation waste, such as empty fruit bunches also palm fronds, as compost can improve soil quality. This study provides essential baseline information for better and more sustainable land management, supporting long-term oil palm productivity